Efektivitas Metode Hypnoteaching Dalam Pembelajaran Keterampilan Berbicara Bahasa Jerman Peserta Didik Fase F SMA Negeri 1 Salatiga - Yolanda Azahra; Iman Santoso (Nexus Publishing, 2024)
This research aims to determine: 1) the difference in learning achievement of German speaking skills of Phase F students of SMA Negeri 1 Salatiga between those taught using the Hypnoteaching method and those taught using the Conventional method, 2) the effectiveness of using the Hypnoteaching method in learning German speaking skills of Phase F students of SMA Negeri 1 Salatiga. The data source of this study is the assessment of Phase F students' speaking skills at SMA Negeri 1 Salatiga. The design of this study is the Pretest and Posttest Control Group Design. Data analysis using the t-test. The results showed that the t_count of 4.115 was greater than the t-table of 2.036, at a significance level of α = 0.05. Calculation with an effectiveness weight of 10.27%. Thus, it can be said that there is a significant difference in the learning achievement of German speaking skills of Phase F students of SMA Negeri 1 Salatiga who are taught using the Hypnoteaching method and the Conventional method, and the use of the Hypnoteaching method is effective in learning German speaking skills of Phase F students of SMA Negeri 1 Salatiga.